2011
DOI: 10.1038/nm.2542
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell–based tissue regeneration is governed by recipient T lymphocytes via IFN-γ and TNF-α

Abstract: Stem cell-based regenerative medicine is a promising approach for tissue reconstruction. Here, we showed that pro-inflammatory T cells in the recipients inhibited bone marrow mesenchymal stem cell (BMMSC)-mediated bone formation via T helper 1 (Th1) cytokine interferon (IFN)-γ induced down-regulation of runt-related transcription factor 2 (Runx-2) pathway and tumor necrosis factor (TNF)-α-regulated BMMSC apoptosis. TNF-α converted IFN-γ-activated non-apoptotic Fas to a caspase 3/8-associated apoptotic signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
621
5
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 574 publications
(661 citation statements)
references
References 38 publications
32
621
5
3
Order By: Relevance
“…Bone marrow cells were flashed out from bone cavity of fe- murs and tibias with 2% heat-inactivated fetal bovine serum (FBS; Equitech-Bio, Kerrville, TX, USA) and cultured with α minimum essential medium (α-MEM, Invitrogen) supplemented with 20% FBS, 2 mM L-glutamine (Invitrogen), 55 μM 2-mercaptoethanol (Invitrogen), 100 U/ml penicillin, and 100 μg/ml streptomycin (Invitrogen), as previously reported [43].…”
Section: Isolation Of Mouse Bone Marrow Mscsmentioning
confidence: 99%
“…Bone marrow cells were flashed out from bone cavity of fe- murs and tibias with 2% heat-inactivated fetal bovine serum (FBS; Equitech-Bio, Kerrville, TX, USA) and cultured with α minimum essential medium (α-MEM, Invitrogen) supplemented with 20% FBS, 2 mM L-glutamine (Invitrogen), 55 μM 2-mercaptoethanol (Invitrogen), 100 U/ml penicillin, and 100 μg/ml streptomycin (Invitrogen), as previously reported [43].…”
Section: Isolation Of Mouse Bone Marrow Mscsmentioning
confidence: 99%
“…However, largely because there are few data on mechanism, the role of IFNG is unclear as to whether it induces or inhibits differentiation in these cells (39,40). Now, with the data on the mechanism reported here, it is clear that IFNG is a potent checkpoint inhibitor of osteogenesis, and we can understand how it can function as a master regulator of differentiation for the many different stem cells that have IFNG receptors.…”
Section: Ifng Is a Primary Checkpoint For Cytokine-induced Odontoblasticmentioning
confidence: 84%
“…By grafting bone marrow MSCs subcutaneously in a mouse model, using hydroxyapatite tricalcium phosphate (HA-TCP) particles as a carrier, we confirmed that recipient T-cells inhibit MSC-based bone regeneration using the same mechanism observed in vitro. Based on this finding, we further applied systemic infusion of Tregs, or local administration of aspirin, to reduce IFN-γ and TNF-α concentration, and found that both methods can markedly alleviate IFN-γ/TNF-α-induced MSC apoptosis, thereby improving MSC-mediated subcutaneous bone formation (Liu et al, 2011). Furthermore, we showed that local aspirin treatment and systemic Treg infusion are able to significantly improve MSC-mediated calvarial bone repair via inhibition of IFN-γ and TNF-α levels (Liu et al, 2011).…”
Section: Lymphocytes Affect Msc Survival and Differentiationmentioning
confidence: 99%
“…Based on this finding, we further applied systemic infusion of Tregs, or local administration of aspirin, to reduce IFN-γ and TNF-α concentration, and found that both methods can markedly alleviate IFN-γ/TNF-α-induced MSC apoptosis, thereby improving MSC-mediated subcutaneous bone formation (Liu et al, 2011). Furthermore, we showed that local aspirin treatment and systemic Treg infusion are able to significantly improve MSC-mediated calvarial bone repair via inhibition of IFN-γ and TNF-α levels (Liu et al, 2011). Therefore, treatment with aspirin or Tregs may provide promising approaches for improving MSC-based tissue engineering (Fig.…”
Section: Lymphocytes Affect Msc Survival and Differentiationmentioning
confidence: 99%